Changes in culture and matchmaking behavior: online dating on Tinder - Fransisca Benedicta Avira Citra Paramita (Indonesian Journal of Social Sciences, 2021)
Whether humans drive technology or technology capable of moving human life systems is still a debate and a contradiction in the thinking of some humans. Technological progress in Indonesia itself cannot be denied. What is feared is that the diversity of cultures and languages in Indonesia is threatened with extinction. One of the cultures that used to be felt in Indonesia was the culture of finding a mate. In ancient times, searching for a mate used traditional methods or more thick and trusting through elements of the surrounding culture and customs. However, with the development of technology began to erode the custom of finding a mate, which was replaced by technology's role. In this study, researchers focused on how technology replaces the role of culture, customs, and religion in finding someone's mate using social media applications. The theory used is to use determinism technology theory, which tries to prove that technology is starting to replace humans' role. This study took interviews with eight female informants from different ethnicities, religions, and ages. This study indicates that human trust in technology is now greater than the culture or customs that are still held firmly by the Indonesian people.